Training intervention effects on cognitive performance and neuronal plasticity—A pilot study - Wiebking, Christine; Lin, Chiao-I; Wippert, Pia-Maria (Frontiers in Neurology, 2022)
The aim of the current pilot study was to examine the effects of sensorimotor training for nonspecific chronic low back pain on (1) cognitive performance; (2) structural-functional brain areas related to pain processing (functional connectivity); and (3) the relationship between functional connectivity and subjective variables (pain and depression). 662 volunteers with nonspecific chronic low back pain were randomly allocated to a unimodal (sensorimotor training), multidisciplinary (sensorimotor training and behavioural therapy) intervention, or to a control group. A subsample (n=21) participated in the here presented pilot study. Measurements were at baseline, during (3 weeks) and after intervention (12 weeks and 24 weeks). Cognitive performance was measured by Trail Making Test, functional connectivity by MRI. Pain perception and depression were assessed by the Von Korff questionnaire and the Hospital and Anxiety. Group differences were calculated by univariate and repeated ANOVA measures and Bayesian statistics; correlations by Pearson's r. Change and correlation of functional connection were analyzed within a pooled intervention group (uni-, multidisciplinary group). Participants with increased pain intensity at baseline showed higher functional connectivity between pain-related brain areas used as ROIs in this study. Though small sample sizes limit generalisation, cognitive performance increased in the multimodal group. Increased functional connectivity was observed in participants with increased pain ratings. Pain ratings and connectivity in pain-related brain regions decreased after the intervention. The results indicate that intervention effects can potentially be achieved in the cognitive and neural domain. The intervention may be suitable for therapy and prevention of nonspecific chronic low back pain.